2019
DOI: 10.1002/hbm.24630
|View full text |Cite
|
Sign up to set email alerts
|

A three‐wave longitudinal study of subcortical–cortical resting‐state connectivity in adolescence: Testing age‐ and puberty‐related changes

Abstract: Adolescence is the transitional period between childhood and adulthood, characterized by substantial changes in reward‐driven behavior. Although reward‐driven behavior is supported by subcortical‐medial prefrontal cortex (PFC) connectivity, the development of these circuits is not well understood. Particularly, while puberty has been hypothesized to accelerate organization and activation of functional neural circuits, the relationship between age, sex, pubertal change, and functional connectivity has hardly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
80
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 81 publications
12
80
1
Order By: Relevance
“…Adolescence. Our results showing significant developmental decreases in vmPFC -NAcc coupling, evident in both reward and rest contexts, are in agreement with previous resting state and task-based fMRI studies showing developmental decreases in PFC -NAcc connectivity Fareri et al, 2015;Porter et al, 2015;Supekar et al, 2009;Van Duijvenvoorde et al, 2016;Van Duijvenvoorde et al, 2019, but see Van Den Bos et al, 2012 who showed increases in task-related connectivity between late childhood and early adolescence). These changes may be influenced by changes in DAergic processing and may contribute to known changes in adolescent reward processing.…”
Section: Decreased Vmpfc -Nacc Connectivity May Reflect a Developmentsupporting
confidence: 93%
“…Adolescence. Our results showing significant developmental decreases in vmPFC -NAcc coupling, evident in both reward and rest contexts, are in agreement with previous resting state and task-based fMRI studies showing developmental decreases in PFC -NAcc connectivity Fareri et al, 2015;Porter et al, 2015;Supekar et al, 2009;Van Duijvenvoorde et al, 2016;Van Duijvenvoorde et al, 2019, but see Van Den Bos et al, 2012 who showed increases in task-related connectivity between late childhood and early adolescence). These changes may be influenced by changes in DAergic processing and may contribute to known changes in adolescent reward processing.…”
Section: Decreased Vmpfc -Nacc Connectivity May Reflect a Developmentsupporting
confidence: 93%
“…Data at the second longitudinal time point (T2) were collected approximately 2 years later from 254 of the original participants (mean age = 16.07 years, age range = 9.92-26.62 years; 131 female). Although previous articles have published findings from the BrainTime study's restingstate data (van Duijvenvoorde, Westhoff, de Vos, Wierenga, & Crone, 2019;Peters, Peper, van Duijvenvoorde, Braams, & Crone, 2017;Peters, Jolles, van Duijvenvoorde, Crone, & Peper, 2015;van Duijvenvoorde, Achterberg, Braams, Peters, & Crone, 2015) and data from its two tasks separately (Schreuders et al, 2018;Braams & Crone, 2017a, 2017bPeters, Van der Meulen, Zanolie, & Crone, 2017;Braams, Peper, Van Der Heide, Peters, & Crone, 2016;Peters, van Duijvenvoorde, Koolschijn, & Crone, 2016;Braams, van Duijvenvoorde, Peper, & Crone, 2015;Braams, Peters, Peper, Güroğlu, & Crone, 2014;Peters, Braams, Raijmakers, Koolschijn, & Crone, 2014;Peters, Koolschijn, Crone, van Duijvenvoorde, & Raijmakers, 2014), this is the first study integrating all of the functional task and rest data from BrainTime's first two longitudinal time points.…”
Section: Participants and Experimental Tasksmentioning
confidence: 99%
“…Pubertal status showed a faster growth rate in females compared to males. Although self-reported questionnaires are sensitive to inaccuracies (Dorn et al, 2006), the pattern observed has been replicated in other populations (Braams et al, 2015;Wierenga et al, 2018;van Duijvenvoorde et al, 2019). Pubertal scale scores showed a faster growth rate in females around level 2 and 12 years of age compared to males.…”
Section: Puberty and Neurodevelopmental Trajectoriesmentioning
confidence: 68%
“…This scale allows to take into account sex-specific patterns of puberty development even at the same chronological age. Children under 10 years old were set to level 1 of the PDS, as previous studies have shown similar values at these ages (Hibberd et al, 2015;van Duijvenvoorde et al, 2019). Missing values corresponding to 8 time-points (4 females) were estimated with two age-smooth splines by sex with a Generalized Additive Mixed Model (GAMM) following van Duijvenvoorde et al (2019).…”
Section: Pubertal Statusmentioning
confidence: 99%
See 1 more Smart Citation